2020
DOI: 10.15567/mljekarstvo.2020.0105
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of volatile compounds from milk to curd during manufacturing of Mozzarella

Abstract: The aim of this study was to investigate the evolution of the volatile compounds (VOC) from milk to curd during mozzarella manufacturing, in connection with the technique used for curd acidification (traditional = natural whey starter fermentation; industrial = direct acidification by citric acid addition). Overall, 40 compounds were identified from the entire set of samples, belonging to different chemical classes. All compounds detected in milk were also found in the curd, but at much higher concentration. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…3-methylbutanal in cheese often arise from the conversion of the corresponding amino acid (isoleucine) by the LAB activity [ 46 ], and its concentration suggests a more marked microbial activity with respect to the samples without sorbic acid. This hypothesis was supported by the huge increase of ketones in Ctr and Ex, mainly connected to the formation of acetoin (1839.57 and 1512.48 μg kg −1 respectively, versus 7.8 and 7.4 μg kg −1 in So and Ex-So) that commonly derives from LAB and yeasts metabolism [ 47 ]. Ethyl acetate and ethyl butanoate increased much more in Ex, in connection with a higher presence of ethanol, which represents the limiting factor for their formation [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…3-methylbutanal in cheese often arise from the conversion of the corresponding amino acid (isoleucine) by the LAB activity [ 46 ], and its concentration suggests a more marked microbial activity with respect to the samples without sorbic acid. This hypothesis was supported by the huge increase of ketones in Ctr and Ex, mainly connected to the formation of acetoin (1839.57 and 1512.48 μg kg −1 respectively, versus 7.8 and 7.4 μg kg −1 in So and Ex-So) that commonly derives from LAB and yeasts metabolism [ 47 ]. Ethyl acetate and ethyl butanoate increased much more in Ex, in connection with a higher presence of ethanol, which represents the limiting factor for their formation [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The VOC detected in the DOC samples was found to be qualitatively and quantitatively lower than those reported in other pasta-filata cheeses (Verzera et al, 2010;Sulejmani and Hayaloglu, 2016;Natrella et al, 2020;Sabia et al, 2020). This could be mainly due to a low level of lipolysis and proteolysis in DOC during the…”
Section: Changes In Volatile Aroma Compoundsmentioning
confidence: 54%
“…However, we also found many other VOC which could have contributed to the final aroma of the product. Among these, PCA‐HGR had the highest abundance of 2,3‐dimethylpentanal, hexanal, 2‐pentenal, 2‐heptenal, octanal, 1‐octen‐3‐ol, 2‐ethyl‐1‐hexanol, benzyl alcohol, ethyl acetate, 6 methyl‐5‐hepten‐2‐one and acetic acid, which could confer green, fatty, fruity, pungent and earthy notes, and PCA‐HGO had the highest abundance of 2‐octenal, 2‐nonenal, 3‐hexen‐1‐ol, 1‐heptanol and α‐phellandrene, which could confer fatty, green, herbal, terpenic and woody odor notes 60,61 . Finally, PCA‐HG had the highest abundance of decanal, ethanol, 1‐penten‐3‐ol, maltol, dimethyl disulfide and γ‐caprolactone, giving theoretically pleasant odors of floral, fatty, citrus, alcoholic and grass, and the unpleasant odors of rancid and sulfur 62 …”
Section: Discussionmentioning
confidence: 99%
“…Among these, PCA-HGR had the highest abundance of 2,3-dimethylpentanal, hexanal, 2-pentenal, 2-heptenal, octanal, 1-octen-3-ol, 2-ethyl-1-hexanol, benzyl alcohol, ethyl acetate, 6 methyl-5-hepten-2-one and acetic acid, which could confer green, fatty, fruity, pungent and earthy notes, and PCA-HGO had the highest abundance of 2-octenal, 2-nonenal, 3-hexen-1-ol, 1-heptanol and ⊍-phellandrene, which could confer fatty, green, herbal, terpenic and woody odor notes. 60,61 Finally, PCA-HG had the highest abundance of decanal, ethanol, 1-penten-3-ol, maltol, dimethyl disulfide and γ-caprolactone, giving theoretically pleasant odors of floral, fatty, citrus, alcoholic and grass, and the unpleasant odors of rancid and sulfur. 62 The sensory evaluation results confirmed that the unpleasant flavor (legumes or beany flavor) was masked by the addition of spices as the mean score of spices was 'mild', while the mean scores of the legumes was 'low' and sourness and astringent were absent in the samples.…”
Section: Volatile Profile and Sensory Features Of Pcasmentioning
confidence: 99%